Kesulitan Membaca Permulaan Siswa Sekolah Dasar dalam Pembelajaran Bahasa Indonesia - Rahmy Febriani Ritonga; Fatimah Siregar; Akhiril Pane (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study aims to map the difficulties in early reading among elementary school students through an indexed literature review. A qualitative method was used by analyzing ten journals indexed in SINTA and Non-SINTA. The findings indicate that early reading difficulties are multidimensional, covering technical, cognitive, and motivational aspects. The causes stem from internal factors, such as cognitive ability, psychological conditions, and specific disorders, as well as external factors, including family support, teaching methods, and the availability of learning media. Effective strategies include structured teacher interventions, the use of multisensory learning media, daily reading habits, parental involvement, and individualized learning approaches. Success in early reading is influenced by early stimulation, continuous practice, engaging literacy corners, and active parental support. This study provides a comprehensive understanding of early reading difficulties and recommended strategies to enhance students’ foundational literacy.